2015
DOI: 10.1155/2015/384148
|View full text |Cite
|
Sign up to set email alerts
|

Pyramidal Lobe of the Thyroid Gland: Surgical Anatomy in Patients Undergoing Total Thyroidectomy

Abstract: Background. Anatomic variations, the presence of the pyramidal lobe (PL), may impact completeness of thyroidectomy and effect of surgical treatment. Method. This study included 166 patients who underwent total thyroidectomy. The anterior cervical region between the thyroid isthmus and the hyoid bone was dissected during thyroid surgery. The incidence, size, and anatomical features of the PL were established in these patients. Results. The incidence of PL was 65.7%. No gender difference was found for PL inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 14 publications
1
28
3
1
Order By: Relevance
“…Thyroid gland abnormality was found in this research as a result of the emergence of pyramidal lobe (8.8 %). In the previous research conducted with different sample groups, with the diversities of the cadavers' nationalities and the places and the times of study, showed that the percentages of thyroid gland abnormality (18-66 %) were higher than the one found in this research (Braun et Begum et al;Joshi et al;Ozgur et al, 2011;Zivic et al, 2011;Park et al, 2012;Cengiz et al, 2013;Mortensen et al, 2014;Veerahanumaiah et al;Gurleyik et al, 2015;Rajkonwar & Kusre). In 2017, there was a reported case with pyramidal lobe emergence (Gurleyik et al) (Table III).…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Thyroid gland abnormality was found in this research as a result of the emergence of pyramidal lobe (8.8 %). In the previous research conducted with different sample groups, with the diversities of the cadavers' nationalities and the places and the times of study, showed that the percentages of thyroid gland abnormality (18-66 %) were higher than the one found in this research (Braun et Begum et al;Joshi et al;Ozgur et al, 2011;Zivic et al, 2011;Park et al, 2012;Cengiz et al, 2013;Mortensen et al, 2014;Veerahanumaiah et al;Gurleyik et al, 2015;Rajkonwar & Kusre). In 2017, there was a reported case with pyramidal lobe emergence (Gurleyik et al) (Table III).…”
Section: Discussionmentioning
confidence: 48%
“…In another study, however, this abnormality was found at 21.6 % (Ranade et al). These thyroidal gland abnormality are susceptible to the operation of radiology physicians and surgeons in thyroidectomy and tracheostomy performances (Gurleyik et al;Sinos & Sakorafas, 2015;Kaklamanos et al, 2017). Being well acknowledge about the thyroidal anatomical change crucial step prior to giving treatment to the patients with thyroid gland abnormality (Rajkonwar & Kusre).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, overlooked embryologic remnants may lead to recurrence. Considering the potential risk of recurrence from PL, its intraoperative identification and excision may decrease the risk of recurrence [6][7][8]. ZT should be excised after careful dissection on the posterior side of the gland considering the proximity of the tubercle to the recurrent laryngeal nerve [9].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this variation may encumber the completeness of total and subtotal thyroidectomy, which is usually the treatment of choice for benign and malignant diseases of the thyroid gland [3]. This is the first case of total thyroidectomy on a patient with DPL reported in Greece.…”
Section: Introductionmentioning
confidence: 99%